Sport Pedagogy Recent Approach to Technical-Tactical Alphabetization - Serra-Olivares, Jaime (IntechOpen, 2018)
There are several teaching sports approaches for school-age sports practitioners. However, relatively few models have a substantial theoretical and scientific foundation. In this sense, the present work aims to serve as an introduction on which to support the didactical process of a Non-Linear Pedagogy of games teaching, as described in the first chapter. A comparison between the traditional approach of sports teaching and the Teaching Games for Understanding model within the Slovak Republic context is exposed. Subsequently, experience in the Sport Education model in Finland is presented. Then, research regarding teachers' experiences with the Cooperative Learning model at different ethnic, cultural, and socioeconomic backgrounds is developed. Finally, an example of the Non-Linear Pedagogy program is used in Malaysia.